Psychometric Characteristics of the Kalam Cognitive Test (KCT): An Andrich Rating Scale Analysis - Kriswantoro; Amelia, Rizki Nor (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The science of Kalam is one of the compulsory courses for prospective Islamic teachers, and mastery of this material is very important. Therefore, the measurement instrument used must have good psychometric characteristics to accurately reflect the abilities of prospective Islamic teachers. The purpose of this study is to analyze the psychometric characteristics of the Kalam Cognitive Test (KCT), which has been developed with the Andrich Rating Scale and assisted by the Winsteps program. The research, which was conducted in the spring semester of the 2022–2023 academic year, involved 44 prospective Islamic religion teacher students in the Islamic Religious Education Study Program at Jambi Ma'arif Islamic College who were selected through cluster random sampling techniques. The results of the analysis show that the KCT has good psychometric characteristics in terms of fulfilling the assumptions of the analysis, item reliability, person reliability, and item difficulty level. Related to the rating scale analysis, it can also be concluded that all rating scale categories have met the required criteria so that they have functioned properly.